2010
DOI: 10.1016/j.cell.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Factors Control Histone Variant H3.3 Localization at Specific Genomic Regions

Abstract: Summary The incorporation of histone H3 variants has been implicated in the epigenetic memory of cellular state. Using genome editing with zinc finger nucleases to tag endogenous H3.3, we report genome-wide profiles of H3 variants in mammalian embryonic stem (ES) cells and neuronal precursor cells. Genome-wide patterns of H3.3 are dependent on amino acid sequence, and change with cellular differentiation at developmentally regulated loci. The H3.3 chaperone Hira is required for H3.3 enrichment at active and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

97
1,293
5
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,114 publications
(1,454 citation statements)
references
References 92 publications
97
1,293
5
9
Order By: Relevance
“…It is likely that the loading mechanism of FACT and H3.3 differs between Drosophila and mammals and possibly between different loci. It has been proposed that H3.3 is generally deposited to transcribed regions by the H3.3-specific histone chaperone HIRA (29,35). However, we previously showed that HIRA knockdown does not affect CSR (8).…”
Section: Discussionmentioning
confidence: 86%
“…It is likely that the loading mechanism of FACT and H3.3 differs between Drosophila and mammals and possibly between different loci. It has been proposed that H3.3 is generally deposited to transcribed regions by the H3.3-specific histone chaperone HIRA (29,35). However, we previously showed that HIRA knockdown does not affect CSR (8).…”
Section: Discussionmentioning
confidence: 86%
“…13 ATRX and DAXX form a dimer that acts as a histone chaperone to deposit histone variant H3.3 to GC-rich regions of the genome, including the telomeres, and plays important roles in maintaining telomere stability. [14][15][16] It is hypothesized that dysfunction of the dimer leads to telomere instability, increased telomere homologous recombination, and ultimately, alternative lengthening of telomeres. Subsequent studies have reported frequent ATRX loss (but not DAXX loss) in astrocytoma, leiomyosarcoma, dedifferentiated liposarcoma and other tumor types, and the loss of ATRX has been highly correlated with the alternative lengthening of telomeres phenotype.…”
mentioning
confidence: 99%
“…However, recent genome-wide studies found that H3.3 is also deposited at heterochromatin regions such as retroviral elements, telomeres and pericentromeres (Elsasser et al, 2015;Goldberg et al, 2010). For instance, studies of mouse ES cells showed that the DAXX-dependent deposition of H3.3 at telomere regions maintains telomere integrity, a situation which is essential for self-renewal of these cells.…”
Section: The Regulation Of Chromatin Dynamics By Variant H33mentioning
confidence: 99%
“…Meanwhile, H3.3 is also distributed in other regions such as cis-regulatory elements Goldberg et al, 2010;Mito et al, 2007), and plays an important part in the regulation of gene expression . However, the chaperon that is responsible for deposition of H3.3 at these regions remains to be identified (Filipescu et al, 2013;Goldberg et al, 2010;Szenker et al, 2011). Taken together, these results suggest that H3.3 is deposited across the genome by dedicated chaperone pathways with respect to chromatin contexts ( Figure 1B).…”
Section: The Properties Of H33 Compared With Its Canonical Counterpartsmentioning
confidence: 99%
See 1 more Smart Citation